2019
DOI: 10.18632/oncotarget.26792
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of targeting CD138 with a chimeric antigen receptor for the treatment of multiple myeloma

Abstract: After unprecedented successes in B-cell malignancies, chimeric antigen receptor T cells have recently been investigated for the treatment of multiple myeloma. Chimeric antigen receptor targeting T cells B-cell maturation antigen (BCMA) on malignant plasma cells have led to impressive clinical responses in recent trials. However, BCMA-negative relapses have been observed, supporting the need for complementary treatment strategies. Here, we explored the feasibility of targeting CD138 (syndecan-1), a surface mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 44 publications
1
52
0
1
Order By: Relevance
“…In 2019 Sun et al provided data that strongly support the aforementioned clinical trials [105]. They used retroviral vector-mediated transduction of anti-CD138 scFvs from the CD138 antibody (BT062) to develop anti-CD138 CAR T cells.…”
Section: Cd138mentioning
confidence: 96%
“…In 2019 Sun et al provided data that strongly support the aforementioned clinical trials [105]. They used retroviral vector-mediated transduction of anti-CD138 scFvs from the CD138 antibody (BT062) to develop anti-CD138 CAR T cells.…”
Section: Cd138mentioning
confidence: 96%
“…Clinical trials with anti-BCMA CAR-T cells have shown efficacy in certain patients [101]. Other potential targets for CAR-T cell therapy include CD138 [102], CD38 [103], and SLAMF7 [104], which are all cell surface proteins expressed on MM cells. Other strategies include monoclonal antibodies directed to cell surface receptors with current drugs approved for targeting SLAMF7 [105] and BCMA [106].…”
Section: The Intersection Of Llpc and MMmentioning
confidence: 99%
“…Four of them achieved stable disease (SD) and 1 progression (PD). Toxicity of the treatment was limited [8,9].…”
Section: Cd38mentioning
confidence: 99%